Frequency of Different Patterns of Fractures Presented in Accidents and Emergency Department of Mayo Hospital Lahore: Fractures Presented in Accidents and Emergency Department - Naseer, Muhammad Kashaf; Inam, Khair Ul; Naqvi, Syed Maisum Raza; Naqshband, Mumraiz Salik; Niazi, Suhail Niaz Khan; Masood, Faisal; Sarfraz, Ahmed Humayun (Pakistan Journal of Health Sciences, 2024)
Emergency departments encounter various fracture patterns that are influenced by factors such as age, injury mechanism, and underlying health conditions. Objectives: To investigate the frequencies of different fracture types and patterns, and thus assess the work burden observed in the emergency departments of Mayo Hospital, Lahore. Methods: This study was conducted at the Orthopedic Section of the Emergency Department of Mayo Hospital, Lahore between 1st January to 31st December 2022. Data were obtained from registers used to make entries of the patients in the Orthopedic section. All patients were divided into a pediatrics group (up to 12 years of age) and an adult group (above 12 years of age). The adult group was further divided into male and female groups. Results: 29190 (85.03%) were adults and 5136 (14.97%) were pediatric patients. Among the adult patients, 21048 (72.11%) were males and 8142 (27.89%) were females while in the pediatrics age group, 3378 (65.78%) were boys and 1758 (34.22%) were girls. Overall, the lower limb was more commonly fractured than the upper limb (52.88 % versus 32.16%) and the most frequently fractured bone was the tibia (19.99%). The leading cause of injury is Road Traffic Accidents (64.21%) followed by machine injuries (9.28%) and falls (7.85%). Patients aged 21 to 30 years were frequently affected (19.77%). Conclusions: It was concluded that daily, nearly one hundred fractures were reported to the Emergency department of Mayo Hospital Lahore. Resources need to be improved to cope with continuous quality care for these patients.